Implementation of an Activity-Based Costing (ABC) approach for analyzing the cost of community-based rehabilitation activities for disabled children - Hasan, Haliza; Syed Junid, Syed Mohamed Al Junid; Wan Puteh, Sharifah Ezat; Abdul Aziz, Aznidah Firzah; Muhammad Nur, Amrizal; Mohd Nordin, Nor Azlin; Jaafar, Nurul Anisah (Prince of Songkla University, 2017)
INTRODUCTION: Activity-based costing (ABC) is a method to estimate costs by time motion activity. All activities run in the program were evaluated.